Respuesta :

Step-by-step explanation:

5. Let the equation of the line be y = mx + c

m = (6-15)/(2-(-1)) = -3

sub (2, 6) and m = -3:

6 = -3(2) + c

c = 12

Equation of the line: y = -3x + 12

6. Let the equation of the line be y = mx + c

y-intercept of 7 means c = 7

y = mx + 7

x-intercept: value of x when y = 0

therefore, sub (4, 0):

0 = m(4) + 7

m = -7/4

Equation of the line: y = -7/4x + 7

this is a topic on coordinate geometry. If you wish to explore more into this topic you can give me a follow on Instagram (learntionary) I'll be posting the notes for this topic soon and will also be posting other topics' notes and some tips :)